Retail Sector in India - Jain, Alpika (2006)
This dissertation provides detailed information about the present scenario of retailing in India. It describes the highly fragmented retail environment in India and trends in selling through different retail formats. It examines the political,economical,social and technical factors affecting the growth in retail industry. It also highlights the opportunities and threats faced by the industry. Key issues such as globalisation in retail and foreign direct investment in India are analyzed in depth. It throws light on the costs and benefits associated with foreign direct investment. It explores the role of the Government of India in the industrys growth and the need for further reforms. The report concludes with the proposed strategies and reforms government should follow to boost up the retail sales.